Promoting Student Success and DE&I in Experiential Education at an HBCU: STEM Lab Internship Programs : A low-cost lab internship program at Delaware State University provides a cost-effective model for increasing experiential opportunities for STEM students. - Perchiniak, Erin; Fees, Joseph; Silver, Alexa (Experiential Learning and Teaching in Higher Education, 2023)
Over the past four years, a Howard Hughes Medical Institute (HHMI) Inclusive Excellence grant supported Delaware State University (DSU) to increase student success and foster faculty development in the STEM (Science, Technology, Engineering, and Mathematics) fields. One component of this grant has provided students, particularly early sequence (freshman and sophomores), the opportunity to participate in a lab internship program. This program has provided students with access to vital research experience and removed some of the barriers for student opportunities, particularly for minority and first-generation students, in STEM fields. The internship program is rooted in principles of diversity, equity, and inclusion and is a cost-effective model for increasing experiential opportunities for STEM students. This paper will share the logistics and inclusive parameters of the program, survey data from student and faculty mentors, as well as highlight the benefits of incorporating an early experiential learning opportunity for students in STEM fields. The paper demonstrates the steps to create a low-cost lab program and how future internships experiences can be designed with diversity, equity, and inclusion as core principles.